2018
DOI: 10.1111/jopr.12940
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Mastication on the Retention and Wear of Locator Attachments in a Flat Mandibular Ridge Model

Abstract: Within the limitations of this in vitro study, simulated mastication seems to significantly affect the extra-light blue Locator inserts but not the more-retentive ones. The transparent and pink inserts may require less frequent replacements and could therefore be recommended under clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is difficult to attribute this reduction to dimensional changes of the inner core or the inner diameter of the inserts, since no significant correlations were found between changes in retentive forces and wear-related measurement changes. An explanation of these unexpected changes in retention could be related to surface deterioration of the insert surface with subsequent increase in surface roughness through micromechanical friction (15). In agreement with this finding, Kleis et al (16) demonstrated that Positioner attachments lost some of their retentive capacity over time as a result of wear of the patrix Positioner parts.…”
Section: Discussionmentioning
confidence: 77%
“…It is difficult to attribute this reduction to dimensional changes of the inner core or the inner diameter of the inserts, since no significant correlations were found between changes in retentive forces and wear-related measurement changes. An explanation of these unexpected changes in retention could be related to surface deterioration of the insert surface with subsequent increase in surface roughness through micromechanical friction (15). In agreement with this finding, Kleis et al (16) demonstrated that Positioner attachments lost some of their retentive capacity over time as a result of wear of the patrix Positioner parts.…”
Section: Discussionmentioning
confidence: 77%
“…ERA ® , Locator ® and CM Loc ® RD decrease significantly in long term retention, and in particular for Locator ® (66 to 75% of their initial retention) compared to CM Loc ® (32 to 47%) after 30,000 IRC (16 years) [ 29 ], and this appears earlier for ERA ® RD (85% after 1000 IRC/1 year) [ 21 , 23 ]. In general, for Locator ® , a significant decrease in retention is even observed during the first 10 to 20 IRC, but retention loss remains not significant after 100,000 CC (3 months) [ 13 , 46 ]. Nevertheless, a progressive decrease is observed until 1000 to 2000 IRC (i.e.,1 to 2 years of clinical service) [ 5 , 10 , 13 , 35 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It seems that improving the stability of the maxillary overdenture leads to an increased need for adjustments in the less stable mandibular overdenture. Moreover, in this study, all participants first received the blue, extra‐light retention Locator inserts, which might also affect the wear of the inserts (Tehini et al., 2019). The pink or transparent inserts were used after the first change in ascending order and might need replacing less often and might therefore be recommended for use.…”
Section: Discussionmentioning
confidence: 99%